Crisis on the Coast and Hinterland Assessing India's East Coast with Geomorphological, Environmental and Remote Sensing and GIS Approaches - Paul, Ashis Kumar; Paul, Anurupa (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This contributed volume assesses the state and future of India's East Coast through a wide variety of chapters grouped by methodology and approach. Part I: Assessment through Geomorphological Approaches describes geomorphological diversities of the eastern shorelines of India, Coastal Modelling System- SMC and morphodynamics of Odisha coast, Paleo shorelines and beach ridge chenier formations of Subarnarekha delta, seasonal sediment budget of Chandrabhaga beachdune system, Beach stage and dune stage modelling Mandarmoni coast, drainage characters of South Andaman Islands, coastal foredune morphology and sediment of Odisha and West Bengal, Geo-archaeological pieces of evidence of ancient coastal environment, coastal sediment characters, beach ridge formation in the chenier coast, and geomorphological changes of ancient ports and harbours in the shoreline of West Bengal. Part II: Assessment through Environmental Approaches addresses various environmental assessment techniques of mangrove sensitivity to the sea level rise process in the Sundarban, land degradation of the hinterland drainage basins, the riparian environment of the coastal drainage basins, agricultural adaptability in response to climate variability in the coastal areas of West Bengal, forest degradations of the lateritic upland tracts, coastal tourism potentialities in Odisha and West Bengal, Climate variabilities and agricultural modifications in the hinterland areas of West Bengal districts, the tidal flat environment of Sagar Island, landforms and Geomorphosites for the promotion of Geotourism in South Andaman Perils of Premature Reclamation of Sundarban, marine litter in the coastal regions of West Bengal and Odisha on flora, fauna and humans, Ground water contamination due to saline water encroachment in coastal Andhra Pradesh and Spatio-temporal changes in the Hugli estuarine environment and coastal hazards and flood risk of southwestern Sundarban. Part III: Assessment through Remote Sensing & GIS Approaches uses the aforementioned techniques in service of exploration of monitoring health of Mangrove forest, Geomorphological analysis of the coral fringed coasts of Andaman, hydrological and morphological variations of Ichhamati Tidal estuary, multivariate analysis of coastal vulnerabilities, geography of tourism resources in Andaman group of islands, tourism climate index with application geospatial techniques, diversity of landscape ecology in the coastal blocks of Purba Medinipur, overwash vulnerability in Odisha coast, livelihood security index of the coastal communities, managing coastal squeeze response and wetland loss in the estuarine coastal tract of West Bengal, environmental effects of historical land reclamation process in the Sundarban, and emerging environmental problems of coastal urbanization in Digha, Kanthi, and Haldia.
Chapter 1: Geomorphological diversity and sea level rise vulnerabilities on India's East Coast -- Chapter 2: Near Shore Morphological Alteration through Sediment Dynamics: An Integrated Software Based (Coastal Modelling System- SMC) Approach for Deltaic Balasore Coast, Odisha, India -- Chapter 3: Shoreline change and associated beach ridge chenier formations in the Subarnarekha Delta region, India -- Chapter 4: Estimation of seasonal sediment budget of Chandrabhaga beach-dune system, Bay of Bengal, India -- Chapter 5: Evidence of an ancient coastline in the southwest Sundarban, India, with investigation of geoarchaeological remains -- Chapter 6: Beach stage and dune stage modelling approach in the geomorphological evolution of beach dune landscapes, Mandarmoni coast, India -- Chapter 7: Spit dynamics and hydro-geomorphic process along the Chilika lagoon estuary -- Chapter 8: Barrier spit morphology and beach ridge formation in the Subarnarekha delta: A review of the protective functions of the low-lying coast -- Chapter 9: The degradation of coastal habitats in Andhra Pradesh and Tamil Nadu: An environmental approach -- Chapter 10: Mangrove sensitivity to the ephemeral rise of sea waters in the Western Sundarban -- Chapter 11: Land Degradation and its Management Approaches in the Middle and Lower Courses of the Subarnarekha River Basin, India -- Chapter 12: Issues and Management Strategies of the Riparian Corridor of the Dulung River Basin, India -- Chapter 13: The importance of shoreline beaches for coastal tourism potential and their diversities on the Odisha coast -- Chapter 14: Climate variability and agricultural modifications in Purulia and Bankura districts of West Bengal -- Chapter 15: An assessment of the changing environmental factors of estuarine tidal flats in Sagar Island -- Chapter 16: Temporal and spatial changes in the Hugli estuarine environment: A review of Nayachara Island -- Chapter 17: Assessment of hazards and flood risks in the southwestern Sundarban -- Chapter 18: Perils of Premature Reclamation: Case studies from the Indian Sundarban -- Chapter 19: Inventory of landforms and Geomorphosites for the promotion of Geotourism in South Andaman Island, India -- Chapter 20: Historical and Geomorphological background of Ancient Khejuri- Hijili and Tamralipta ports in South Bengal -- Chapter 21: An assessment of the impacts of marine litter in the coastal regions of West Bengal and Odisha on flora, fauna and humans -- Chapter 22: Ground water contamination due to saline water encroachment in coastal Andhra Pradesh, with particular emphasis on the morphological units -- Chapter 23: Geomorphological analysis of the coral fringed coasts of Andaman and Nicobar islands using Geo-spatial techniques -- Chapter 24: Mangroves in cyclone-battered Sundarban, India: A Geoinformatics based multi-temporal study -- Chapter 25: Multivariate analysis of coastal vulnerabilities for Tamil Nadu coast using Remote Sensing & GIS techniques -- Chapter 26: Managing the coastal squeeze and wetland loss in Sagar Island in a sustainable framework using Geospatial Techniques -- Chapter 27: Assessment of Tourism Carrying Capacity for the sustainable tourism development of South Andaman, India -- Chapter 28: Tourism Climate Index (TCI) for assessing the favorable period for tourism recreation activities with the application of Geospatial techniques -- Chapter 29: Assessment of diversity in landscape ecology in parts of the Purba Medinipur coastal District, West Bengal, with Geospatial technology -- Chapter 30: Overwash vulnerabilities in Chilika lagoon with barrier spit morphology of Odisha coast, an assessment with Remote Sensing approach -- Chapter 31: Changing Livelihood Security Index along the coastal belt of Purba Medinipur district, an assessment using Spatial Information Systems -- Chapter 32: Urban sprawling and its emerging consequences in response to climate variability: a study in coastal urban areas of Digha, Contai and Haldia using remote sensing approach.
Keywords: Environment; Geography; Geographic information systems; Environmental management; Geomorphology; Environmental Sciences; Geography; Geographical Information System; Environmental Management; Geomorphology